Development of new technologies and their practice for sustainable farming systems in the Mekong Delta : (JIRCAS, 2003)
The present project covers the second phase of the JIRCAS initiative to develop sustainable farming systems in area. It emphasizes practical aspects such as on-farm trials of the technologies, economic evaluation of new technologies and so on.